Community involvement in obstetric emergency management in rural areas: a case of Rukungiri district, Western Uganda - Ogwang Simon; Najjemba Robinah; Tumwesigye Nazarius; Orach Christopher (BMC, 2012)
Abstract Background Maternal mortality is a major public health problem worldwide especially in low income countries. Most causes of maternal deaths are due to direct obstetric complications. Maternal mortality ratio remains high in Rukungiri district, western Uganda estimated at 475 per 100,000 live births. The objectives were to identify types of community involvement and examine factors influencing the level of community involvement in the management of obstetric emergencies. Methods We conducted a descriptive study during 2nd to 28th February 2009 in rural Rukungiri district, western Uganda. A total of 448 heads of households, randomly selected from 6/11 (54.5%) of sub-counties, 21/42 (50.0%) parishes and 32/212 (15.1%) villages (clusters), were interviewed. Data were analysed using STATA version 10.0. Results Community pre-emergency support interventions available included community awareness creation (sensitization) while interventions undertaken when emergency had occurred included transportation and referring women to health facility. Community support programmes towards health care (obstetric emergencies) included establishment of community savings and credit schemes, and insurance schemes. The factors associated with community involvement in obstetric emergency management were community members being employed (AOR = 1.91, 95% CI: 1.02 - 3.54) and rating the quality of maternal health care as good (AOR = 2.22, 95% CI: 1.19 - 4.14). Conclusions Types of community involvement in obstetric emergency management include practices and support programmes. Community involvement in obstetric emergency management is influenced by employment status and perceived quality of health care services. Policies to promote community networks and resource mobilization strategies for health care should be implemented. There is need for promotion of community support initiatives including health insurance schemes and self help associations; further community sensitization by empowered community based resource persons rather than health workers and improvement in quality of health care can contribute towards effective management of obstetric complications.